Sistema de seguimiento por imágenes asistido por GNSS-GPS:TV Tracker - García Bravo, Santiago; Curetti, María; Arri, Gabriela; Pucheta, Julián; Mathé, Ladislao (2021)
Fil: Bravo, Santiago García. Instituto Universitario Aeronáutico Córdoba; Argentina.